Prehypertension is associated with early complications of atherosclerosis but not with exercise capacity. (15th January 2017) - Jung, Mi-Hyang; Ihm, Sang-Hyun; Lee, Dong-Hyeon; Chung, Woo-Baek; Jung, Hae Ok; Youn, Ho-Joong
Abstract: Background: Prehypertension has a high risk of progression to hypertension, and intensive lifestyle modification including regular exercise is recommended for the management of prehypertensive individuals. However, data on the association between exercise capacity and hypertension status are limited. Therefore, we aimed 1) to define the characteristics of prehypertension, focusing on metabolic aspects and exercise capacity, and 2) to elucidate determinants of exercise capacity in healthy individuals without hypertension. Methods: We retrospectively identified 741 normotensive healthy subjects (mean age, 52.6 ± 8.8 years; 57.9% men) who underwent consecutive cardiopulmonary exercise testing. The participants were categorized into two groups: the optimal blood pressure (BP) (systolic BP < 120 mmHg and diastolic BP < 80 mmHg, n = 364) and prehypertension (systolic BP 120–139 mmHg and/or diastolic BP 80–89 mmHg, n = 377) groups. Exercise capacity was assessed with peak oxygen consumption. Results: The prehypertension group showed metabolic syndrome characteristics, and had increased left ventricular mass index and impaired diastolic function. However, no significant differences in exercise capacity were found between the optimal BP and prehypertension groups (peak VO2, 25.3 ± 7.2 vs. 25.8 ± 7.3 mL/kg/min, p = 0.327). Age, resting heart rate, and fat percentage were identified as independent determinants of exercise capacity ( p < 0.001 for all). Conclusions: Prehypertension is associated with metabolic disarrangement and preclinical target organ damage but not with exercise capacity. Exercise capacity is determined by age, resting heart rate, and body composition in relatively healthy individuals who do not have hypertension.